Head and neck venous malformations, a specialist centres experience of management and treatment outcomes - Conor Gordon; Amit Prasai (Elsevier, 2021)
Introduction: Venous malformations are congenital abnormalities affecting veins. These conditions present a challenging condition for both the patient and clinician. When presenting in the head and neck region these conditions can cause a variety of differing symptoms including airway compromise, compression of nerves and vessels as well as cosmetic issues. Leeds Teaching Hospitals Trust (LTHT) Head and Neck vascular malformations MDT was established in 2008 with the aim of providing a specialist care to patients affected by these and other vascular malformations. The MDT consists of maxillofacial and ENT surgeons as well as paediatricians, radiologists and a specialist nurse. Methods: We retrospectively analysed electronic patient records and identified those who attended the head and neck vascular malformations MDT at LTHT with venous malformations. 87 patients were identified as being suitable for the study. Data was collected on multiple parameters. Results: The youngest patient attending the MDT was 1 month old and the oldest was 84 years old. The average age at presentation was 19 years old. Of the 87 patients 48 were males and 39 were females. Ultrasound was the most popular initial imaging modality followed by MRI. 48 patients had injection sclerotherapy as their primary treatment. 2 patients underwent primary surgical excision of their venous malformation. 37 patients had no treatment. Conclusions: Head and neck venous malformations are complex conditions and benefit from a multidisciplinary approach. The vascular anomalies MDT at LTHT provides this to all patients managed in Leeds via experienced clinicians who can offer multiple treatment modalities.